ADVANCES IN TOTAL SYNTHESIS OF ALTERNARIC ACID: AN ANTI-FUNGAL AND PHYTOTOXIC NATURAL PRODUCT - Sajjad Ahmad; Muhammad Yousaf; Ameer Fawad Zahoor; Matloob Ahmad; Zulfiqar Ali khan; Muhammad Arslan Rashid (Journal of the Chilean Chemical Society, 2017)
Alternaric acid is characterized as 1,4-diene, possessing (E)-1,2-disubstituted alkene known for nanomolar phytotoxic and antifungal activities. This article highlights the major synthetic approaches attempted towards the total synthesis of alternaric acid reported by three groups (Ichihara & coworkers, Trost & coworkers and Johnson and Slade) which involved novel pathways for the rapid construction of this functionalized natural molecule.